Enhanced degradation of diesel-contaminated soil using organic wastes - A, Dadrasnia; P., Agamuthu (Malaysian Journal of Science, 2010)
This study was carried out to enhance the biodegradation of diesel fuel in soil contaminated with 10% (w/w) diesel fuel amended with 10% tea leaf (IL), soy cake (SC), potato skin (PS) for a period of 3 months under laboratory condition. At the end of 84 days, the highest percentage of oil biodegradation (76%) was recorded in soil amended with SC; 64% and 53% were recorded with soil amended with PS and TL respectively, while only 27% of oil degraded in control treatment. Hydrocarbon utilizing bacteria ( HUB ) counts were high in all organic wastes amended treatments, ranging from 45x106 CFU/g to 90 x106 CFU/g of soil compared to unamended control soil (4x106 CFU/g to 8 x106 CFU/g of soil ). The count in amended soil was significantly different at (P< 0.05) compared to unamended soil. The results obtained showed 90%, 80% and 60% seed germination in remediated soil contaminated with 10% diesel fuel and amended with SC, PS and TL respectively, over the period of 84 days. The results show the high potential of SC for enhanced biodegradation of hydrocarbon in oil contaminated soil.